Green Synthesis Nanopartikel Perak-Gelatin dengan Ekstrak Limbah Kulit Manihot esculenta untuk Aplikasi Surface-Enhanced Raman Scattering (SERS) - Aprilia, Septi; Shofiyatun, Siti; Fitriyah, Isnanik Juni; Erlangga, Soni Yunior (Alpatih Harapan Semesta, 2024)
This study aims to develop a green synthesis method of silver nanoparticles (AgNPs) by utilising cassava (Manihot esculenta) peel waste extract and gelatin as reducing and stabilising agents for Surface-Enhanced Raman Scattering (SERS) applications. This synthesis technique promotes environmentally friendly principles by using natural materials that are easily available, cost-effective, and reduce the use of hazardous chemicals. The synthesis results show that the silver nanoparticles obtained have high stability and are able to increase the intensity of the Raman signal, allowing the detection of molecules at very low concentrations. Characterisation of AgNPs includes analysis using UV-Vis spectroscopy, TEM, XRD, as well as SERS performance measurements. This research shows that green chemistry-based synthesis methods can produce high-quality nanoparticles with high efficiency, so they have the potential to be widely applied in various chemical sensor applications that require high sensitivity.